DisAbility in der Migrationsgesellschaft Betrachtungen an der Intersektion von Behinderung, Kultur und Religion in Bildungskontexten - Konz, Britta; Schröter, Anne (Verlag Julius Klinkhardt, 2022)
The anthology brings together interdisciplinary theoretical and empirical findings on disAbility and migration in educational contexts as well as analyses of the intersectionality of disability, migration and religion in education and society. It strives to interconnect the concerns of migration education, disability studies, and religious education. In doing so, theorizations about narratives of belonging in the migration society as well as possibilities of participation in medical-therapeutic and pedagogical fields of action are carried out. In addition, questions are asked about the necessary competencies of pedagogically active persons. Special attention is paid to research contexts that focus on the perspectives of children and adolescents with disabilities and their parents.